Treatment of acetabular injuries and the consequences (literature review - Oleg K. Chegurov; Il'ia N. Menshchikov (Гений oртопедии, 2018)
Acetabular fractures are often complex injuries and the result of high-energy trauma increasing in recent years with the increased use of high-speed motor vehicles. Acetabular fractures account for 7 to 25 % of all pelvic injuries and are associated with significant morbidity. The complex nature of these fractures requires multi-staged treatment with the usage of various methods of osteosynthesis, their combination including primary reconstructive joint replacement. In spite of the improved techniques and new technologies rehabilitation of the patients is a particularly challenging problem. Material and methods Literature searches were performed on several databases: PubMed, Scopus, еLibrary.ru and others. Search keywords included “acetabular injury”, “consequences of acetabular fracture”, “acetabular osteosynthesis”, “total hip replacement”, “nonunion of acetabulum”, “hip arthroplasty in patients with consequences of acetabular injury”. Objective To do analytical review on the subject “Treatment of consequences of acetabular injuries”. Conclusion Types of acetabular injuries and methods of treatment are described in the available literature. Nevertheless, the findings showed no systemic approach to rehabilitation of the patients and there is a need to improve the existing practice and devise new techniques and algorithms of treatment.